2013
DOI: 10.1158/0008-5472.sabcs13-p2-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P2-11-16: Prospective comparison of prognostic factors in patients starting a third line of chemotherapy for metastatic breast cancer: An ancillary study to the CirCe01 trial

Abstract: Background: Several prognostic factors and composite scores based on either patients general condition and/or usual blood analyses have been described in the setting of advanced metastatic cancers to estimate patients overall survival (OS). Over the past decade, circulating tumor cells (CTC) have been repeatedly reported as being a strong prognostic tool in metastatic breast cancer patients. We took the opportunity of the observational part of a prospective clinical trial (CirCe01, NCT01349842) that included 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, especially in research on liquid biopsies, thresholds of biomarker expression are being used to classify whether the particular biomarker expressions are either present or absent. Assuming that these tools are based on the best available evidence, they may be suitable to facilitate the prioritization of the clinical research agenda when considering different thresholds of the expression a particular biomarker to distinguish different patient subgroups [48].…”
Section: The Potential Of Decision Tools In New Biomarker Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, especially in research on liquid biopsies, thresholds of biomarker expression are being used to classify whether the particular biomarker expressions are either present or absent. Assuming that these tools are based on the best available evidence, they may be suitable to facilitate the prioritization of the clinical research agenda when considering different thresholds of the expression a particular biomarker to distinguish different patient subgroups [48].…”
Section: The Potential Of Decision Tools In New Biomarker Discoverymentioning
confidence: 99%
“…Several studies have reported on the discordance in ER/PR/HER2 between tumor needle biopsies and tumor resection. However, most (recent) studies reported on relatively small sample sizes in total, small subgroups of breast cancer patients, or included only patients diagnosed at a single hospital [42,[48][49][50]. In the study presented here, we have evaluated the discordance in ER/PR/HER2 between tumor needle biopsy and tumor resection material in the majority of invasive breast cancer patients diagnosed in 2016 and 2017 in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation